Features of traditional Indian construction for sustainability - Murugan, I.; Natarajan, C.; Rajaraman, A. (Journal of Structural Engineering, 2025)
Traditional Indian construction has many features that demonstrate sustainability aspects through their functional and survival aspects against many odds of weather and onslaughts of war for centuries. These are presented in three sections of planning, investigation and design and construction. To bring out the features of three typical constructions chosen in the form of Kathali, Thiruvalluvar Statue and Bruhadeeswarar Temple and discussed.